EL EJERCICIO DEL PODER DE LOS JUECES - González Solano, Gustavo (2023)
Judges play three types of role: governments employee, authorities and legal technician. It makes difficult any scientific activity in relation to the law, and makes imposible, to consider judges function “scientific”.